Use of simultaneous distillation-extraction, supercritical fluid extraction and solid-phase microextraction for characterisation of the volatile profile of Dipteryx odorata (Aubl.) Willd - Bajer, Tomáš; Surmová, Silvie; Eisner, Aleš; Ventura, Karel; Bajerová, Petra (Elsevier Science BV, 2018)
Head-space solid phase microextraction (HS-SPME), simultaneous distillation-extraction (SDE) and supercritical fluid extraction (SFE) were employed to prepare volatile extracts of tonka beans (Dipteryx odorata). A total of 190 compounds were assigned by gas chromatography/mass spectrometry (GC/MS) together in comparison with retention indices. These included 156 (HS-SPME), 77 (SDE) and 36 (SFE) compounds (alcohols, carbonyl compounds, acids, esters, terpenes, terpenoids, lactones, aliphatic and aromatic hydrocarbons, and other non-categorised compounds). Semiquantitative evaluation of individual compounds was performed using gas chromatography coupled with a flame ionisation detector. The main constituent detected in all extracts was coumarin (51-85%, despite the extraction method) belonging to the group of lactones. A comparison was made among the three methods in terms of volatile profiles, categorisation of compounds and representation of individual groups of compounds. Extracts prepared by HS-SPME were rich in alcohols, carbonyls and acids than other extracts. Results can provide essential information for the application of different treatment of tonka beans in flavor industries.
Užití simultální destilace-extrakce, extrakce nadkritickou tekutinou a mikroextrakce tuhou fází pro charakterizaci profilu těkavých látek Dipteryx odorata (Aubl.) Willd
Keywords: Head-space solid phase microextraction; Simultaneous distillation-extraction; Supercritical fluid extraction; Tonka beans; Volatile; Tonka; Mikroextrakce tuhou fází; Simultánní destilace-extrakce; Extrakce nadkritickou tekutinou; Těkavé sloučeniny